(untitled) (Per Musi, 2015)
This paper studies high registers of heavy metal singing based on the voice profile analysis scheme (VPAS) protocol. Its main objective is to provide a scientific basis for a theme which is subjectively treated by the musical literature. Two professional and two amateur singers were recorded for the perceptual analysis. Their vocal productions were analyzed intra- and inter-singers by VPAS experienced judges (vocal coaches, speech therapists, phoneticians). Results indicate that the two groups of singers use distinctive articulatory strategies in singing at high registers.